Modelos de Cohousing como ferramenta para a construção de habitação sustentável - Leonardo David da Silva Rodrigues (2022)
This dissertation has as its starting point the study of cohousing as a model that intends to rethink contemporary housing. This model is read in parallel with the themes of sustainability in architecture, whether at a social, environmental or economic level, suggested through the construction of a sense of community and sharing. The cohousing is defined according to its recurring characteristics, highlighting the participatory process as an essential methodology for the development of the project, and the presence of common facilities in the building, in response to the specific wills of the residents. Additionally, we contextualize the emergence of cohousing, which originated in Denmark in the early 70's, and which evolved, in an initial phase, in the countries of northern Europe; the different ways of organization of the model are thus distinguished. As a means of interpreting the theoretical views presented, we propose a reflection on five case studies in an european context that address the analyzed premises of cohousing. These projects are studied under three scales of inhabiting - the place, the building and the private unit - which makes it possible to make an analogy between the different approaches and establish common points. Above all, it is important to understand the different spheres in the transition between public and private spaces, with the common space being the hinge between them. Finally, it is intended to briefly address the issue of collaborative housing in Portugal, in order to understand how, in the future, cohousing or its principles could be applied in the housing development of the country.